BY MULTIPHASE FLOWS IN THE FORMATION AND WELL IN RELATION TO THE THERMOMETRY OF WELLS - Bobonazarov, Dilshod; Hotamov, Jahongir (Физико-технологического образование, 2022)
This substance is widely used in temperatures and pressures in many flow layers in the study of the composition of groundwater, the properties of many reliefs and stratified flows. a lot of work is carried out in higher educational institutions in the direction of physics and geophysics